2018
DOI: 10.7759/cureus.2746
|View full text |Cite
|
Sign up to set email alerts
|

Medication Error Reporting: Underreporting and Acceptability of Smartphone Application for Reporting among Health Care Professionals in Perak, Malaysia

Abstract: Background and objectivesIn Malaysia, the national voluntary non-punitive Medication Error Reporting System (MER-S) has been available since 2009, with compiled reports indicating the underreporting of various medication errors (ME). This survey intends to determine the ME reporting practice among healthcare professionals and the acceptance of ME reporting by utilising smartphone application if it is available.DesignA cross-sectional survey was conducted for two months in 2017 among doctors and pharmacists in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
(37 reference statements)
5
21
0
Order By: Relevance
“…Among the diagnostic errors, delayed diagnosis was high (84.8%), wrong diagnosis, inappropriate investigation and failure to use results as recorded (16.5, 63.9, and 69%, respectively) were listed. Also, failure to provide prophylactic treatment was observed among 69.6% of the healthcare providers; these results are in agreement with previous studies [10,[26][27][28]. This finding is consistent with a report in which medical errors where reportedly the main contributory factors towards the patients harm [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the diagnostic errors, delayed diagnosis was high (84.8%), wrong diagnosis, inappropriate investigation and failure to use results as recorded (16.5, 63.9, and 69%, respectively) were listed. Also, failure to provide prophylactic treatment was observed among 69.6% of the healthcare providers; these results are in agreement with previous studies [10,[26][27][28]. This finding is consistent with a report in which medical errors where reportedly the main contributory factors towards the patients harm [29].…”
Section: Discussionsupporting
confidence: 92%
“…This is quite obvious that one may never report anything about what he/ she does not understand as well as whom, and how to report it. These findings correlates well with a previous report [13,16,[26][27][28]. Guided by the established system analysis of the clinical incidents [30], a comphrensive approach to analyze and investigate medical incident, going beyond the routine identification of the fault and apportioning blame is critical [30].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Only 44.8% of the medical doctors and pharmacists in their study had experience using medical error reporting systems. 22 It is important to keep in mind that even though there is a low rate of incidents reported, this does not mean that only few incidents do really happen. Sari et al showed that in the case note review by trained professionals, 303 patient safety incidents were found during an analysis of a total of 1006 admissions in a large hospital trust in England, while only 54 were recorded by the reporting system.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] This can result in under‐reporting of errors. [ 2,4–6 ] The degree to which voluntary incident reporting typically captures the true incidence of medication errors is difficult to ascertain and subject to high variability. [ 3,7 ] The types of errors most likely to go unreported in incident reporting systems are also unknown.…”
Section: Introductionmentioning
confidence: 99%